Analysis of silica based prosthetic human teeth using 3D printing machine for dental assistance. (2021) - Blesslin Sheeba, T.; Albert Raj, A.; Ravikumar, D.; Sheeba Rani, S.; Vijayakumar, P.; Subbiah, Ram
Abstract: In recent years, most of the peoples are suffering from teeth issues. Increased cavities of the teeth are formed due to these issues. Cavities may lead to the fracturing of human teeth. Such partial dentures and affected teeth can cause patients to experience brutal problems. There is a risk to break teeth when having injuries which can lead to serious patient issues. Doctors tend to substitute original teeth with artificial teeth in order to reduce these issues. These artificial teeth are made up of chromium and zirconium materials in current innovations, which can cause high cost and time-taking processes for the manufacture of artificial teeth by using these types of materials. A new, revolutionary 3D printing technology is being used to prepare artificial teeth to reduce these factors. In this work, an attempt was made to create artificial teeth using Silica material via a 3D printing technique. The prototype model teeth model with silica material was manufactured and it's demonstrates to medical students and patients. Using modeling software (CATIA) and Analysis software (ANSYS) the necessary components were designed and the corresponding results were reported.